Knowledge, Attitude and Practices of Medical Students regarding Needle stick injuries in Villupuram, India – A cross-sectional study - Saravanakumari Arumugham Dhanaraj; Harissh Ganesan (Public Health Review: International Journal of Public Health Research, 2023)
Objective: To determine knowledge, attitude and practices of medical students regarding needle stick injuries. Methods: A cross sectional survey was conducted among the consenting medical students of 2nd, 3rd and 4th years at Government Villupuram Medical College and Hospital, Villupuram, India. Convenience sampling was used. Pre-tested questionnaires were administered to approximately 70% of each class. Data was analyzed using SPSS version 26.0. Associations were assessed using chi-square test and Fisher’s exact test. A p-value of <0.05 was considered as significant. Results: The response rate of the survey was 85.7%. Sixty-one students (33.9%) were from 2nd and 3rd year each while 58 students (32.2%) were from 4th year. More than 85% students from each class were aware of the possibility of acquisition of Hepatitis B, Hepatitis C and HIV from needle stick injuries. Only 16.4% 2nd year students, 29.5% 3rd year students and 36.2% final year students knew the full details of needle stick injury prevention protocols. Curriculum was cited as an important source of information regarding needle stick injuries. Forty-seven (26.1%) students had received a needle stick injury in the past; however, only 14 students (29.7%) had reported the incident either to their consultant or the Infection Control Office. Conclusion: Overall knowledge of medical students regarding various aspects of needle stick injuries improved with seniority in medical college. However, the domains of attitude and practices need to be improved as the frequency of needle stick injuries was also observed to increase with the increasing year of medical education